Pengaruh Kredit Perbankan Terhadap Pertumbuhan Ekonomi dan Hubungannya Dengan Kesejahteraan Masyarakat - Ridha, Irfan; Anjani, Mira; Huda, Misbahul; Firdaus, Mohd Raihan; Ardel, Muhammad; Zarlianda, Muhammad Revicho; Pratama, Muhammad Zaki; Kurniawan, Nauval Fajar; Saputri, Wira Ade (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the effect of credit disbursed by commercial banks on economic growth in Indonesia. The independent variable is used in this research is credit while inflation, investment, infrastructure and labor as a control variable. Using the Static Data Panel method is obtained The estimation results show that the credit disbursed has a significant influence but has a negative relationship caused by unbalanced credit growth and the resulting output. Other variables that have a significant effect and have a relationship positive are inflation and investment, while infrastructure and labor are not significant affect economic growth.